Strengthening Fraternal Compassion through Islamic Journalistic Communication: Ethical Media for Indonesia–Singapore Harmony - Saragih, M Yoserizal (Lafadz Jaya Publisher, 2025)
This study investigates the strategic role of Islamic journalistic communication in promoting fraternal compassion and fostering bilateral harmony between Indonesia and Singapore. In an era shaped by digital polarization and cultural fragmentation, ethical journalism becomes crucial in constructing inclusive narratives and supporting peaceful cross-border relations. The objective of this research is to identify how Islamic values particularly the principle of rahmatan lil-‘alamin (mercy to all creation) inform journalistic practices that contribute to intercultural understanding and regional diplomacy. Using a qualitative, library-based approach, the study examines comparative media discourse from Indonesia and Singapore to highlight patterns of ethical communication that emphasize compassion, responsibility, and soft power engagement. The results reveal that Islamic journalistic communication offers a transformative model to counter stereotypes, foster mutual respect, and enhance transnational solidarity. This study contributes to the broader academic discourse on Islamic media ethics, intercultural dialogue, and religion-based peacebuilding by proposing a theoretical framework for ethical Islamic journalism applicable in other multicultural societies across Southeast Asia.